P1510Values of left ventricular area strain during 4D-strain-stress echocardiography with adenosine triphosphate in healthy subjects - Nelassov, N; Morgunov, M; Doltmurzieva, N; Sidorov, R; Arzumanjan, E; Eroshenko, O; Safonov, D; Kreneva, E; Zatonsky, S (European heart journal, 2019)
Abstract Background Use of adenosine triphosphate (ATP) instead of adenosine in stress echocardiography is more cost-effective. Earlier we have proposed new ATP stress echocardiography algorithm (Figure). This modified algorithm includes 1) stepwise increase in dose of ATP in the absence of signs of adequate vasodilation (decrease in systolic blood pressure and increase in heart rate), 2) triple registration of echocardiographic data sets (before ATP infusion, during phase of adequate vasodilation and 5 minutes after the termination of ATP infusion). Purpose In this study we aimed to a) assess the safety of ATP high doses infusion algorithm, b) determine the values of left ventricular (LV) systolic global and segmental area strain (AS) during 4D-strain-stress echocardiography with ATP in healthy volunteers. Material and methods 13 healthy subjects (male 9, mean age 35.3±11.0 years) underwent ATP LV 4D strain-stress-echocardiography (Vivid E95, AFI technology). Mean values of global and regional (16 segments model) AS were determined. Results 4 subjects appeared to be “non responders” to initial dose of ATP 140 μg/kg/min. In three subjects it was necessary to increase the dose of ATP to 175 and in one to 210 μg/kg/min in order to achieve adequate vasodilation. No major side effects of ATP infusion (complete heart block, bronchospasm, myocardial infarction) were registered and no aminophylline injections were required. In all cases interpretable 4D LV Echo data sets for automatic strain analysis were obtained. Mean values of global systolic AS in healthy individuals before, at time and after ATP infusion were −25.8±4.8, −27.2±4.4 and −25.7±4.8%, respectively. Mean values of systolic AS in each of 16 segments were also calculated (Table). LV segment AS before ATP (%) AS ATP infusion (%) AS after ATP (%) LV segment AS before ATP (%) AS ATP infusion (%) AS after ATP (%) 1 −29.6±11.3 −31.2±11.1 −28.6±8.3 9 −27.8±6.5 −29.3±6.8 −30.8±6.0 2 −26.6±8.5 −28.2±4.9 −26.2±7.3 10 −26.1±5.2 −274±5.5 −25.8±6.0 3 −25.6±6.8 −29.6±5.2 −27.2±7.2 11 −25.3±6.1 −26.1±7.5 −24.9±5.3 4 −26.2±7.2 −24.9±9.1 −25.2±6.7 12 −28.1±7.3 −28.5±6.1 −25.3±5.6 5 −26.5±6.8 −29.3±10.9 −24.3±7.7 13 −22.9±6.5 −23.4±6.5 −23.2±6.4 6 −25.2±6.7 −26.0±7.9 −25.5±7.0 14 −25.7±7.6 −28.5±6.0 −26.2±6.8 7 −24.8±7.3 −25.6±6.1 −22.8±6.0 15 −26.5±6.5 −29.8±6.0 −28.5±5.5 8 −25.8±6.6 −26.5±5.6 −25.8±5.5 16 −24.2±7.1 −25.4±6.2 −25.1±6.6 Conclusions 4D strain-stress-echocardiography ATP infusion algorithm is safe and well tolerated by patients. Values of LV systolic global and segmental AS in healthy subjects were determined.